Interaksi Faktor Eksternal dengan Siklus Finansial di Indonesia - Yollit Permata Sari; Isra Yenni; Doni Satria (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aims to interact global financial market fluctuations, commodity price fluctuations and capital flows to determine which factors interact with the cycle in Indonesia the most. The data used is secondary data from official publications, namely Bank Indonesia for data on capital flows and bank credit, the International Monetary Fund (IMF) for international commodity price index data and the global financial market valatility index (VIX). The analysis period in this study is the first quarter of 1993 to the fourth quarter of 2018. The results of the study using the correlation index show that the cycle of capital flows in Indonesia is carried out by global finance and The movement of commodity prices causes the flow of funds that enter the Indonesian economy to be largely short-term, so it tends to have acyclical interactions with bank credit to the business world and is slightly more procyclical for credit to non-business fields. Credit to non-business fields is dominated by bank credit, which is allocated to consumption credit and has a short term.